Penguatan Publikasi Ilmiah Dosen Melalui Kiprah Pustakawan Perguruan Tinggi - Endang Fatmawati (FPPTI Jawa Tengah, 2017)
Librarians as educational staff in universities have a wide role among theacademic community. Increased competence for librarians and collaborationis the basis for their existence to be required by the partners of librarians(lecturers, researchers, students) so that the librarian’s profession becomesuseful to them. Especially in the middle of the onslaught of the digital eratoday, the library as the heart of universities is expected to have a “addedvalue” in improving publications, especially academic people and in generalare people outside the campus. Regardless of the rapid access to information,the existence of a college library will not be replaced in the breath ofthe educational process. Librarians can take positions to become agents insupporting the strengthening of lecturer scientific publications and institutionalvisibility through publication to reputable journals.